Multiple sclerosis in pregnancy: meeting the challenges - Chaudhary, Bhupendra; Rajput, Rashmi Basvantsing; Chaudhary, Ansh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Multiple sclerosis being a chronic, autoimmune inflammatory disease of central nervous system with its common and uncommon semiology has a predilection for women of child bearing age. The stressful period of pregnancy is further complicated with presence of multiple sclerosis. Overall multiple sclerosis has stabilising effect on pregnancy especially in its second and third trimester but adversely affects the post-partum period with increasing relapse rate. This is related with intense immune response triggered by marked changes in levels of circulating hormones. A better understanding of anti-natal, natal and post-partum effect of multiple sclerosis helps us to decide for institution or continuation of disease modifying drugs which are generally associated with favourable outcome.